2012
DOI: 10.7494/drill.2012.29.4.463
|View full text |Cite
|
Sign up to set email alerts
|

Prognosticating fire hazards in goafs in Polish collieries

Abstract: has been carried out of the AGH project No. 11.11.210.244 and within the framework of research task No. 3 under the title Elaboration of the Mesaurement Principles and Research of Mine Air Parameters for the Assessment of Methane and Fire Hazard in Underground Mining Hard Coal executed within the framework of strategic research project under the title Improvement of Work Safety in Mines (Contract No.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
7
0
3
Order By: Relevance
“…A significant problem in forecasting fire based on the gas content in the mine is that propylene and ethylene may also subject to sorption on coal. Numerous studies have demonstrated that the above gases flowing through the coal seam may become trapped by physical or chemical sorption in the coal porous structure [11][12][13]. The sorption process refers to the phenomenon occurring at the solid-gas interface.…”
Section: Introductionmentioning
confidence: 99%
“…A significant problem in forecasting fire based on the gas content in the mine is that propylene and ethylene may also subject to sorption on coal. Numerous studies have demonstrated that the above gases flowing through the coal seam may become trapped by physical or chemical sorption in the coal porous structure [11][12][13]. The sorption process refers to the phenomenon occurring at the solid-gas interface.…”
Section: Introductionmentioning
confidence: 99%
“…That indicates that coalbeds sharing these properties are useless in the context of potential CO 2 sequestration, which is broadly described in the literature as CO 2 storage in a deep saline aquifer. However, in the case of coalbeds, most publications on the subject of CO 2 sequestration (in the area of experimental testing) are focused on sorption tests and establishing the influence of relevant parameters (coal rank, maceral content, porosity, and moisture content) on sorption capacity. In most cases, sorption tests are performed on grainy samples or on samples in the dust form. This approach makes the experimental procedure less time-consuming (the sorption equilibrium is promptly established), although a question arises whether the sample crushing should not destroy the porous structure, and hence, the experimental results may not be directly related to the conditions prevailing in situ . In the case of coal expansion tests, the samples to be tested must not be crushed.…”
Section: Introductionmentioning
confidence: 99%
“…Coal is a porous material of highly developed inner surface and presence of micro- and sub-micropores, enabling sorption of vapors and gases. Gases released in the process of coal self-heating adsorb on coal while migrating through workings. The resulting concentrations measured in mine air are underestimated, which may negatively affect the assessment of the fire hazard.…”
Section: Introductionmentioning
confidence: 99%